Real Time IoT Application of Urban Garden Design - P, Sindhu; G, Leena Giri (International Journal of Computer Sciences and Engineering, 2020)
Gardening is a common pastime for people who love nature. Plants always requires a careful and continues monitoring. Most of the time it will turn into a responsibility. Sometimes garden owner need to go out for a while, then garden may keep on unattended. Internet of thing can give a possible solution for this problem. Environmental condition of the garden can be monitored continuously by using an electronic technology in the garden. Using IoT (Internet of Things), environmental condition in the garden can be monitor through the internet. Gardening is a very exciting to do. So I was very interested in making a project related to it. Nowadays people will enjoy gardening by using an IoT application to it (smart Garden). Moreover the important task here is making the project very simple so that anybody can use this in their garden. In this proposed project garden monitoring system is developed. Here the multiple nodes are designed to collect data from garden and sent to the main node that will upload the data to server where people can assimilate all the condition of their garden.